Handlungsempfehlung zeitlich begrenzter Therapieversuch in der Neurointensivmedizin: Leitlinien und Empfehlungen - Alonso, Angelika; Rogge, Annette; Schramm, Patrick; Münch, Urs; Jöbges, Susanne (Die Anaesthesiologie, 2025)
Many acute brain disorders are associated with acute disorders of consciousness. In an emergency situation, life-saving measures are usually taken first and intensive care is initiated. If there is no significant improvement with recovery of consciousness in the first few days, very complex decision-making situations arise regularly. In neurointensive care, a time-limited therapy trial (TLT) is an important structuring element in treatment planning and communication, as a binding agreement between the treatment team and the patient or legal representative on a treatment concept for a defined period of time. Due to the prolonged neurological rehabilitation phase, the TLT in neurointensive care can also last weeks or months. This often requires interdepartmental communication (acute/rehabilitation/long-term care), re-evaluation and implementation in neurointensive care. The recommendations include the definition, empirical evidence and implementation suggestions for a TLT for critically ill neurointensive care patients.
Online publiziert: 17. März 2025
Gesehen am 27.05.2025